Saberes profissionais e práticas com intencionalidade pedagógica: um estudo sobre o professor de creche - Lizardo, Lilian de Assis Monteiro (2020)
The nursery teaching is a thematic that has his own specification, it agreed of the action field and dialogues with the development of babies and small children, characterizing the construction of their professionalism. The purpose of this research is thus to work together of the nursery group of teachers to build a formative process, in context, that aims on enrichment of babies and small children learning practices. Creating, together with teachers, a sequence of activities in different areas of the early childhood education curriculum that provides different experiences. Firstly, we sought to a theoretical subsidies where allowed us to understand how nursery teaching has been legitimized throughout the institution's history and how curricular practices has been constructed by dialogues between authors like Sacristán (2000), Kishimotto ( 1986), Kramer (2005). Then, it was proposed a training course to a group of teachers at the nursery in São Paulo city, one formative path reflect on the formative way babies and small childres have been learning. The methodology used to collect the data, was participant observation, it was proposed fifteen formative meetings divided into modules of theory, planning and reflection. In the results, we noted that the knowledge of early childhood teachers comes from professional practice and dialogue with more experienced teachers, however the teachers were aware of the theoretical and practical relation, becouse the theorists were contextualized in their teaching practice, and this is more clear within it´s context formation. Another point is that, there is a feeling of fear when proposing activities for babies and children, from an allergic reaction to aspects related as physical security, delineating a positive and negative character, as it can inhibit innovation in the teacher's planning. In the three modules we managed to deploy the concept of reflection-action-reflection in the training of teachers, in order , in the context which they work, to visualize, recognize and solve everyday problems faced of a critical reflection on their actions, their teaching intentionality and their responsibility toward the development and learning of different subjects in the educational community, including families, and this occurred in a process of interaction and collaboration. Therefore, it can be concluded, the possibility to propose a formative experience in the real contexts of education, and that a path of teacher training can affect in a learning path for the baby and the young child in order to establish a theoretical and practical relationship. There are specificities in the professional field of the daycare teacher that must be considered in his continuing education. The teacher only uses some methodology in his classroom, if it makes sense to him in a way of innovation and results collection. There is a lack of a quality standard in the national level, because this some research reports negatively on daycare place, in favor of the development of the baby and child, a fact that we did not see in this research because the daycare is committed to a community learning